Use of territory and financial valuation: the Cosan Group and the Brazilian sugar-energy sector - Silva, Laís Ribeiro; Pereira, Mirlei Fachini Vicente (Sociedade & Natureza, 2023)
The structural changes that have occurred in contemporary capitalism, brought new conditions for the use of territory in Brazil. Consequently, it can be observed the insertion of new agents from the financial sphere, notably investment funds, corporate investors, and high net-worth individuals, who started to participate, directly and indirectly, in the productive processes in various sectors that take place in the Brazilian territory. This process was evaluated in this paper, through the empirical situation of Cosan Group, the main controller of the Brazilian sugar-energy sector (production of sugarcane and sugarcane derivatives).  Our analysis was based on secondary data on the agricultural and agro-industrial production of this group, as well as the strategies and characteristics related to the financialization of the company (such as initial public offering, investor behaviour, among others) and financial issues, using information obtained from public and private databases. The analysis of the use of territory by the Cosan Group makes it possible to identify the transformations associated with the insertion of this agent into the current dynamics of financialization of the economy and the inherent territorial implication of this process. The strategies of the use of territory adopted by the Cosan Group, in the current context of financial accumulation, were mainly guided by the need for financial valuation, which occurred fundamentally through the mobilization of public funds and the territorial expansion of productive activities.